PENDIDIKAN KESEHATAN DALAM PENGELOLAAN HIPERTENSI PADA LANSIA DI POSBINDU BOKESAN NGEMPLAK SLEMAN DIY - Gongo Prihatmono, Ignasius; Fina Aryu Puspasari, Scholastica (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Cardiovascular disease is the leading cause of mortality. The highest prevalence of cardiovascular disease is hypertension. Hypertension prevalence increases in 10 years and WHO predicts that it will always increase until 2030. Hypertension management is needed to prevent any complication and improve patient’s ability in their daily activity. Knowledge about hypertension management is based of healthy lifestyle that affected their quality of life. Objective: this study focused on determining the impact of education on respondent’s cognitive, affective, and psychomotor ability. Methods: this study occupied quasi-experimental design, which involve 40 respondents, divided into 2 groups i,e intervention group and control group (20 respondents each). Results: the majority of respondents were male (62.5%), aged 55-64 (50%), middle education (47.5%), non- smoker (55%), had no diet (62.5%). after 4 weeks, significant differences were found in cognitive, affective and psychomotor level before and after intervention in intervention group (p=0.002; p=0.012; p=0.001). compared to control group, there are significant differences in cognitive and psychomotor level (p=0.028; p=0.013). respondents’ characteristics that impacted on the dependent variable were education level, smoking habit, exercise, coping mechanism. Conclusion: education is an effective intervention to improve cognitive and psychomotor level of people with hypertension. Keywords: Education, hypertension, cognitive, psychomotor